2017
DOI: 10.20937/rica.2017.33.04.09
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Pollution Assessment of Mining Wastes and Soils From Former Silver Amalgamation Area in North-Central Mexico

Abstract: Mining wastes and soils from Cedral, San Luis Potosí, Mexico, were studied to assess mercury (Hg) pollution in areas of historical silver (Ag) amalgamation and in areas where amalgamation mining wastes were recently reprocessed for Hg and Ag recovery. The total, soluble and bioaccessible Hg concentrations from eight mining waste and nine soil cores were determined at varying depths, which fluctuated from the surface up to 1.0 m depth. The total Hg concentrations in the mining wastes samples ranged from 8 to 54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…To achieve the objective of this study, Hg concentration data of representative sources as tailings samples and their associated impacted soils, previously reported by part of our research team (Leura-Vicencio 2017;Leura-Vicencio et al 2017), were assessed. In addition, soil samples from the entire urban area of Cedral previously reported by Morton-Bermea et al (2015) were also considered.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To achieve the objective of this study, Hg concentration data of representative sources as tailings samples and their associated impacted soils, previously reported by part of our research team (Leura-Vicencio 2017;Leura-Vicencio et al 2017), were assessed. In addition, soil samples from the entire urban area of Cedral previously reported by Morton-Bermea et al (2015) were also considered.…”
Section: Methodsmentioning
confidence: 99%
“…Mercury concentration data for the metallurgical residues and soil samples from Cedral were obtained from previous work reported by our research team (Leura-Vicencio 2017;Leura-Vicencio et al 2017). For our study, the results of the uppermost sections (0-10 cm) of three sampling points of reprocessed material from the processing facilities from Jesús María were selected.…”
Section: Mercury Sourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…The total concentrations of Hg in mining residues varied between 8 and 548 mg/kg, while in soils the concentrations were in a range of between 1 and 116 mg/kg. It was found that 80% of the soil samples analyzed exceeded the maximum permissible limit of Hg for land for residential use established in Mexican regulations (Leura Vicencio et. al., 2017).…”
Section: Introductionmentioning
confidence: 93%